Assessment of an institutional guideline for vancomycin dosing and identification of predictive factors associated with dose and drug trough levels - Gu, Q; Jones, N; Drennan, P; Peto, TEA; Walker, AS; Eyre, DW (Elsevier, 2022)
Objectives To evaluate the effectiveness of an antimicrobial guideline for vancomycin prescribing deployed using electronic prescribing aid and web/phone-based app. To define factors associated with guideline compliance and drug levels, and to investigate if antimicrobial dosing recommendations can be refined using routinely collected electronic healthcare record data.